2021
DOI: 10.1016/j.sjbs.2021.09.064
|View full text |Cite
|
Sign up to set email alerts
|

Standardization of in vitro micropropagation procedure of Oriental Lilium Hybrid Cv. ‘Ravenna’

Abstract: Micropropagation protocol of Oriental Hybrid Lilium cv. Ravenna was developed using bulb scale segments (Basal and Tip) as explants. Surface sterilization of healthy bulb scales with carbendazim 200 ppm for 30 min, then 0.1 percent mercuric chloride for 10 min, then 70% ethyl alcohol for 30 s was superior to all other treatments in recording highest culture asepsis (77.08%) and higher explant survival (86.12%). Explant survival was higher in basal segments (88.54%) compared to tip segmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 23 publications
2
21
0
Order By: Relevance
“…Combined sterilant treatments aggravate the phyto-toxic effects leading to reduced explant survival. Similar results were recorded by Rather et al, 2014 , Rafiq et al, 2021 with underground buds of herbaceous peony and Oriental Lilium cv. Ravenna, respectively.…”
Section: Discussionsupporting
confidence: 90%
“…Combined sterilant treatments aggravate the phyto-toxic effects leading to reduced explant survival. Similar results were recorded by Rather et al, 2014 , Rafiq et al, 2021 with underground buds of herbaceous peony and Oriental Lilium cv. Ravenna, respectively.…”
Section: Discussionsupporting
confidence: 90%
“…The sterilization technique is the most significant step for establishing successful in vitro plant regeneration in different crop species. [ [49] , [50] , [51] ]; Gu et al, 2022). Traditional optimization techniques focus on one specific Pareto-optimal solution at a time, transforming the multi-objective optimization problem into a single-objective problem by using multi-criterion decision-making techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Selecting the proper protocol for plant micropropagation is also a crucial factor, which depends on the plant species. For standardization of the micropropagation protocol of any plant species, many studies have been recently reported (e.g., [155][156][157]). Are these challenges facing both developing and developed countries?…”
Section: Discussionmentioning
confidence: 99%